Modular Artificial Bird Nest Interactive Installation: A Practice in Urban Interactive Landscape - Bian, Xinyuan; Duan, Bo; Wu, Di; Jia, Zhiguang; Jin, Mingyu (Journal of Research in Science and Engineering, 2026)
As urban renewal increasingly focuses on the quality of micro-spaces and public participation, landscape installations that integrate playful interaction and ecological care have become a valuable endeavor. This study centers on the design exploration of a "Modular Artificial Bird Nest Interactive Installation," aiming to introduce lightweight interactive nodes into urban public spaces. The installation utilizes connectable hexagonal modules and can be adapted for different bird species by replacing front panels. Its core innovation lies in constructing a three-tier interactive system: an environmental sensing layer collects data inside the nest via sensors; a behavioral sensing layer provides immediate feedback by triggering bird calls; and a virtual interaction layer employs an online platform to facilitate continuous observation logging and community sharing. This design seeks to transform avian activities into a perceptible and engaging experience for residents. Furthermore, the research integrates the concepts of the "Playable City" and "Biophilic Design" to explore the installation's potential applications in everyday settings like community gardens and school campuses. This practice primarily offers a concrete and detailed design methodology for urban interactive landscapes. It aspires that such small-scale interventions can stimulate public awareness of surrounding natural life, thereby infusing the urban environment with greater vitality and interactive enjoyment.